2013
DOI: 10.1002/jgrd.50249
|View full text |Cite
|
Sign up to set email alerts
|

Baffin Island snow extent sensitivity: Insights from a regional climate model

Abstract: [1] Recent modeling efforts suggest that the Little Ice Age (LIA) onset could be explained by a series of four large decadally-spaced volcanic eruptions. At that time, glaciers on Baffin Island advanced and did not retreat until the past century, perhaps due to Arctic and North Atlantic Ocean sea ice feedbacks. To try to determine what parameters sustain snow cover, we investigate the relative impacts of changes in radiation and advection on minimum summer snow extent over Baffin Island. We used the Weather Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…[2012], who found changes in the North Atlantic Ocean circulation following volcanic eruptions that imply strengthened northward oceanic heat transport a decade after major eruptions, which contributes to persistent cooling over Arctic regions on decadal time scales. Berdahl and Robock [2013] supported this result, showing with a regional climate model that the Baffin ice sheet could persist even after volcanic forcing disappeared, given a cooler surrounding Arctic climate. Miller et al [2012] showed that while solar variations may also reinforce Little Ice Age climate variations, they were not necessary to initiate the Little Ice Age.…”
Section: The Cause Of the Little Ice Agesupporting
confidence: 68%
“…[2012], who found changes in the North Atlantic Ocean circulation following volcanic eruptions that imply strengthened northward oceanic heat transport a decade after major eruptions, which contributes to persistent cooling over Arctic regions on decadal time scales. Berdahl and Robock [2013] supported this result, showing with a regional climate model that the Baffin ice sheet could persist even after volcanic forcing disappeared, given a cooler surrounding Arctic climate. Miller et al [2012] showed that while solar variations may also reinforce Little Ice Age climate variations, they were not necessary to initiate the Little Ice Age.…”
Section: The Cause Of the Little Ice Agesupporting
confidence: 68%
“…It also agrees with Zanchettin et al [2012], who found changes in the North Atlantic Ocean circulation following volcanic eruptions that imply strengthened northward oceanic heat transport a decade after major eruptions, which contributes to persistent cooling over Arctic regions on decadal time scales. Berdahl and Robock [2013] supported this result, showing with a regional climate model that the Baffin ice sheet could per sist even after volcanic forcing disappeared, given a cooler surrounding Arctic climate. Miller et al [2012] showed that while solar variations may also reinforce Little Ice Age climate variations, they were not necessary to initiate the Little Ice Age.…”
Section: Small Volcanic Eruptions Of the Past Decadesupporting
confidence: 64%
“…Models with higher peak elevations on Baffin Island tend to have colder mean summer climates. The two models with the coldest climate in the Baffin Island region, CCSM4, and GISS, also represent the high plateaus (400–700 m) [ Andrews et al ., ], elevations critical in fostering and sustaining large snow area change [ Berdahl and Robock , ].…”
Section: Resultsmentioning
confidence: 99%
“…Model resolution, and consequently topography, plays a strong role in determining mean climate over Baffin Island. Critical plateau elevations of 400–700 m, necessary for fostering and sustaining large snow area change [ Berdahl and Robock , ], are only represented in the CCSM4 and GISS models. In more than half of the models, warm summer climates over Baffin Island stunt snow expansion after volcanic eruptions completely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation